Dam anti-seepage material suitable for extreme environment and application method of dam anti-seepage material
By using a combination of self-expanding particles and composite agents in the anti-seepage materials of dams and combined with layered laying technology, the problems of long construction time, high cost and poor anti-seepage effects in the existing technology are solved, and the problem of extreme environments is realized High efficiency anti-seepage performance and durability.
Patent Information
- Application Number
- CN202411215117.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
The existing dam seepage-proof materials have problems such as long construction time, high cost, poor anti-seepage effect and water erosion in extreme environments, especially in emergency repairs and complex geological conditions, which are difficult to meet the long-term anti-seepage requirements.
Using a combination of self-expanding particles, epoxy resin, aqueous polyurethane curing agent and composite agent, the adhesion of the material is enhanced by applying an adhesive film on the surface of self-expanding particles, combined with leakage detection and layered laying method of composite fossil materials. Force and stability to improve anti-seepage performance.
It significantly improves the performance and durability of dam seepage-proof materials in extreme environments, shortens construction time, reduces costs, and enhances the impact resistance and sealing effect of the materials, meeting the long-term seepage-proof needs.
Smart Images

Figure CN119118567A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of dam anti-seepage materials, and in particular, relates to a dam anti-seepage material suitable for extreme environments and an application method thereof. Background Art
[0002] With the continuous development of water conservancy project construction, the safety and stability of dams as important flood control facilities have received more and more attention. Especially under extreme environmental conditions, such as heavy rain, floods, earthquakes and other natural disasters, these extreme environments will cause high water pressure, high osmotic pressure, high flow rate and other conditions in the dams. The anti-seepage performance of the dam is directly related to the safe operation of the entire water conservancy facility.
[0003] Concrete is often used to fill dams for anti-seepage, but this method has some shortcomings. For example, when there are small cracks or pores in the dam, filling with concrete takes a long time, which prolongs the project period, increases costs, and may affect the progress of the entire project. During the concrete filling process, it is necessary to wait for the concrete to fully solidify and harden, which usually takes several days to weeks. During this period, other related construction work cannot be carried out, resulting in delays in the progress of the entire project. Especially in the case of emergency anti-seepage repair, this time delay may bring greater risks.
[0004] In addition, the density and weight of concrete structures are large, so they require additional foundation reinforcement measures in soft foundations or unstable geological conditions, which further increases the complexity and cost of the project. When the soft foundation bears the weight of concrete, it may sink or deform, which will affect the anti-seepage effect and the overall stability of the dam. Therefore, engineers need to strengthen the foundation before construction, such as using pile foundations, cushion layers or other foundation treatment methods. These measures not only increase the construction steps, but also significantly increase the material and labor costs.
[0005] In addition, the application of concrete in complex geological conditions faces other challenges. For example, concrete is susceptible to water erosion in humid or water-saturated geological environments, resulting in material degradation and reduced anti-seepage effect. For this reason, waterproof additives or additional waterproofing measures need to be used during construction, further increasing the difficulty and cost of construction. Even in some extreme environments, the performance of concrete may not meet the requirements of long-term anti-seepage, resulting in the need for regular maintenance and repair. Concrete is often used to fill dams for anti-seepage, but this method has some shortcomings. For example, when there are small cracks or pores in the dam, filling with concrete takes a long time, which leads to a longer construction period, increased costs, and may affect the progress of the entire project. During the concrete filling process, it is necessary to wait for the concrete to fully solidify and harden, which usually takes several days to several weeks. During this period, other related construction work cannot be carried out, resulting in delays in the progress of the entire project. Especially in the case of emergency anti-seepage repair, this time delay may bring greater risks.
[0006] In addition, the density and weight of concrete structures are large, so they require additional foundation reinforcement measures in soft foundations or unstable geological conditions, which further increases the complexity and cost of the project. When the soft foundation bears the weight of concrete, it may sink or deform, which will affect the anti-seepage effect and the overall stability of the dam. Therefore, engineers need to strengthen the foundation before construction, such as using pile foundations, cushion layers or other foundation treatment methods. These measures not only increase the construction steps, but also significantly increase the material and labor costs.
[0007] In addition, the application of concrete in complex geological conditions faces other challenges. For example, concrete is susceptible to water erosion in humid or water-saturated geological environments, resulting in material degradation and reduced anti-seepage effect. For this reason, waterproof additives or additional waterproofing measures need to be used during construction, further increasing the difficulty and cost of construction. Even in some extreme environments, the performance of concrete may not meet the requirements of long-term anti-seepage, resulting in the need for regular maintenance and repair.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a dam anti-seepage material suitable for extreme environments and an application method thereof, and solve the problems raised in the above-mentioned background technology.
[0010] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is: A dam anti-seepage material suitable for extreme environments and an application method thereof, comprising: a mixture of the following raw materials in parts by weight: 30-50 parts of self-expanding particles, 10-20 parts of epoxy resin, 0.2-2 parts of waterborne polyurethane curing agent, and 1-10 parts of compounding agent.
[0011] Optionally, the composite agent is prepared by mixing the following raw materials in parts by weight: 10-25 parts of propylene glycol, 4-10 parts of ethylene glycol, 2-10 parts of silane coupling agent, 1-5 parts of polyimide, 0.1-2 parts of carboxymethyl cellulose, and 0.1-2 parts of surfactant.
[0012] Optionally, the particle size of the carboxymethyl cellulose is 500-800 nm.
[0013] Optionally, the surfactant is polysorbate-80, which is in the form of a yellow to amber viscous liquid.
[0014] Optionally, the cross-linking agent is methylene bisacrylamide, which is in the form of white crystalline powder; the initiator is ammonium persulfate, which is white crystalline powder; and the accelerator is triethanolamine, which is a colorless to light yellow viscous liquid.
[0015] Optionally, the plasticizer is one of phthalate and epoxy soybean oil.
[0016] Optionally, the toughening agent is nano-silicon dioxide, which is a white colloid and does not dissolve in liquid, but forms a colloidal suspension in the liquid.
[0017] Optionally, the method for preparing the dam anti-seepage material comprises the following steps: Step S1: Mix epoxy resin, crosslinking agent and waterborne polyurethane curing agent in proportion, and stir evenly to obtain product ①; Step S2: Add the composite agent to the product ①, continue stirring, and obtain the product ② after it is completely dissolved and stirred evenly; Step S3: coating the obtained product ② on half of the area of the self-expanding particles, and forming a 5-10 mm thick sticky film on the surface of the self-expanding particles after coating.
[0018] Optionally, the preparation method of the composite agent comprises the following steps: Step A1: adding propylene glycol and ethylene glycol to carboxymethyl cellulose in sequence, and continuing to stir, and obtaining a mixed solution after mixing evenly; Step A2: Add the silane coupling agent, polyimide and polysorbate-80 to the mixed solution in sequence, continue stirring, and obtain a composite agent after being evenly dispersed.
[0019] A method for applying the anti-seepage material prepared above comprises the following steps: Step 1): Use leakage detectors and geological radar to inspect the dam to determine the specific location, scope and severity of the leakage area, and estimate the amount of dam anti-seepage materials required based on the size and depth of the leakage area; Step 2): According to the shape, size and geological conditions of the leakage area, plan the laying plan of the composite water fossil material, including the laying layer, thickness and sequence; Step 3): Divide the laying area into the bottom layer, middle layer and top layer according to the leakage area, and add geomembrane between each layer; Step 4): Use large-size gravel for the bottom layer, and small-size gravel for the middle and top layers to increase density and impermeability. The thickness of the bottom layer is 5-10cm, and the thickness of the middle and top layers is 3-5cm. Step 5): Build a working platform above the leakage area, use underwater conveying equipment to transport the self-expanding particles that have just been coated with a sticky film to the leakage area and place them.
[0020] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time: By applying only half of the sticky film to the surface of the self-expanding particles, the sticky film can be tightly attached to the surface of the particles without affecting the expansion performance of the self-expanding particles. This coating method retains the expansion ability of the particles because the surface area of the uncoated portion can still absorb water and expand freely, while the coated portion enhances the adhesion and stability between the particles by forming a tight film layer. The half-coated design does not limit the ability of the particles to absorb water and expand during the expansion process, while also providing additional structural support and impact resistance, thereby significantly improving the overall stability and anti-seepage effect of subsequent bonding. This method effectively combines the unique characteristics of self-expanding particles with the viscosity of anti-seepage materials, ensuring the performance and durability of the material in extreme environments.
[0021] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 It is a schematic diagram of layered laying; Figure 2 Schematic diagram of laying the platform.
[0023] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0024] The embodiment of the present invention discloses an anti-seepage material for dams suitable for extreme environments, which comprises a mixture of the following raw materials in parts by weight: 30-50 parts of self-expanding particles, 10-20 parts of epoxy resin, 0.2-2 parts of waterborne polyurethane curing agent, and 1-10 parts of compounding agent.
[0025] In this embodiment, the composite agent is prepared by mixing the following raw materials in parts by weight: 10-25 parts of propylene glycol, 4-10 parts of ethylene glycol, 2-10 parts of silane coupling agent, 1-5 parts of polyimide, 0.1-2 parts of carboxymethyl cellulose, and 0.1-2 parts of surfactant.
[0026] In this embodiment, the particle size of the carboxymethyl cellulose is 500 nm.
[0027] In this embodiment, the preparation method of the dam anti-seepage material comprises the following steps: Step S1: Mix epoxy resin, crosslinking agent and waterborne polyurethane curing agent in proportion, and stir evenly to obtain product ①; Step S2: Add the composite agent to the product ①, continue stirring, and obtain the product ② after it is completely dissolved and stirred evenly; Step S3: coating the obtained product ② on half of the area of the self-expanding particles, and forming a 5 mm thick sticky film on the surface of the self-expanding particles after coating.
[0028] The preparation method of the composite agent of this embodiment comprises the following steps: Step A1: adding propylene glycol and ethylene glycol to carboxymethyl cellulose in sequence, and continuing to stir, and obtaining a mixed solution after mixing evenly; Step A2: Add the silane coupling agent, polyimide and polysorbate-80 to the mixed solution in sequence, continue stirring, and obtain a composite agent after being evenly dispersed.
[0029] A method for applying the anti-seepage material prepared above comprises the following steps: Step 1): Use leakage detectors and geological radar to inspect the dam to determine the specific location, scope and severity of the leakage area, and estimate the amount of dam anti-seepage materials required based on the size and depth of the leakage area; Step 2): According to the shape, size and geological conditions of the leakage area, plan the laying plan of the composite water fossil material, including the laying layer, thickness and sequence; Step 3): Divide the laying area into the bottom layer, middle layer and top layer according to the leakage area, and add geomembrane between each layer; Step 4): Use large-size gravel for the bottom layer, and small-size gravel for the middle and top layers to increase density and impermeability. The thickness of the bottom layer is 6 cm, and the thickness of the middle and top layers is 4 cm. Step 5): Build a working platform above the leakage area, use underwater conveying equipment to transport the self-expanding particles that have just been coated with a sticky film to the leakage area and place them.
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] In the following examples, the meaning of "ratio" is the proportion of a certain raw material component in the total mass of the raw materials.
[0035] It should be noted that all raw materials used in the examples of the present invention were obtained through commercial channels.
[0036] In the following examples of the present invention, the crosslinking agent is methylene bisacrylamide, which is in the form of a white crystalline powder; the initiator is ammonium persulfate, which is a white crystalline powder; and the accelerator is triethanolamine, which is a colorless to light yellow viscous liquid.
[0037] In the following embodiments of the present invention, the toughening agent is nano-silicon dioxide, which is a white colloid and does not dissolve in liquid, but forms a colloidal suspension in the liquid.
[0038] In the following embodiments of the present invention, the plasticizer is phthalate.
[0039] In the following examples of the present invention, the surfactant is polysorbate-80, and the form of polysorbate-80 is a yellow to amber viscous liquid.
[0040] Example 1: Provided is a dam anti-seepage material suitable for extreme environments, comprising a mixture of the following raw materials in parts by weight: self-expanding particles: 40 parts, epoxy resin: 15 parts, water-based polyurethane curing agent: 1 part, and compounding agent: 5 parts.
[0041] In this embodiment, the composite agent is prepared by mixing the following raw materials in parts by weight: diol: 20 parts, ethylene glycol: 8 parts, silane coupling agent: 5 parts, polyimide: 3 parts, carboxymethyl cellulose (particle size 500 nm): 1 part, and polysorbate-80: 1 part.
[0042] Example 2: A dam anti-seepage material suitable for extreme environments is provided. The materials and preparation methods are the same as those in Example 1, except that the proportion of epoxy resin in Example 2 is 8 parts and the proportion of the compounding agent is 2 parts.
[0043] Example 3: A dam anti-seepage material suitable for extreme environments and a preparation method are provided, which are the same as those in Example 1, except that the proportions of the compounding agent are 14 parts of propylene glycol, 3 parts of alkyl coupling agent, 1 part of polyimide, and 0.5 parts of carboxymethyl cellulose.
[0044] Comparative Example 1: A dam anti-seepage material suitable for extreme environments is provided, and its preparation method is the same as that of Example 1, except that the composite agent is removed.
[0045] Experimental Example 1: Anti-seepage performance test Refer to JTG E50-2006 (Test Procedures for Geosynthetics for Highway Engineering) issued by the Ministry of Transport, and test the samples prepared in Examples 1-3 and Control Examples 1-2 in high temperature and low temperature environments. The test steps are as follows: place the cured samples in a high temperature test chamber at 70°C, keep the samples in a 70°C environment for at least 24 hours to ensure that the samples are fully heated, and use a constant head permeability test device to test in accordance with the provisions of JTG E50-2006. Fix the heated or cooled samples in the permeability cylinder and adjust the constant head device to keep the water head constant. Record the amount of water passing through the sample within a specific time. Calculate the permeability coefficient. Record the permeability coefficient under high temperature and low temperature conditions. The test results are shown in Table 1: Table 1: Test results of permeability coefficient of anti-seepage materials under high and low temperature environments According to the data in Table 1, the anti-seepage materials of Examples 1-3 exhibit lower permeability coefficients under both high and low temperature environments, which are significantly better than the materials of Control Examples 1 and 2. This indicates that the anti-seepage materials with the addition of the composite agent and acrylamide have better anti-seepage performance under extreme environments, so that the anti-seepage effect of the gaps of the self-expanding particles after expansion is better.
[0046] Example 1 has higher anti-seepage performance than Example 2. The main reason is that the proportion of epoxy resin and composite agent in Example 2 is reduced, which reduces the bonding strength and durability of the material, and the reduction in the proportion of composite agent weakens the thickening, strengthening and stabilizing effects of the material. Combining these factors, the permeability coefficient of the material of Example 2 in high and low temperature environments is higher than that of Example 1, so that Example 1 exhibits better anti-seepage effect under extreme environments.
[0047] Embodiment 1 has higher anti-seepage performance compared with embodiment 3, mainly because the ratio of silane coupling agent and carboxymethyl cellulose in embodiment 3 is reduced.The reduction of silane coupling agent reduces the adhesion between material and substrate, and this adhesion is crucial in maintaining the overall strength and stability of the material.Silane coupling agent can form a strong bond with the substrate surface through a chemical bond, thereby improving the anti-peeling and impact resistance of the material.The reduction of carboxymethyl cellulose affects the viscosity and sealing of the viscous film after the self-expanding particles expand.Carboxymethyl cellulose plays a role of thickening and bonding in the material, and its deficiency will cause the material to be unable to form a dense anti-seepage layer during the expansion process, thereby reducing the anti-seepage performance.Combining these factors, embodiment 1 can provide a more excellent anti-seepage effect under extreme conditions.
[0048] Example 1 has higher anti-seepage performance than Control Example 1, while Control Example 1 completely removes the compounding agent, which greatly reduces the anti-seepage performance of the material. The ingredients such as propylene glycol, ethylene glycol, silane coupling agent and carboxymethyl cellulose in the compounding agent play an indispensable role in enhancing the adhesion, flexibility and sealing performance of the material. In Control Example 1 without the compounding agent, the self-expanding particles expand and adhere to each other to form a stable anti-seepage layer under high and low temperature environments, resulting in a significant increase in its permeability coefficient, and the anti-seepage effect is far inferior to that of Example 1.
[0049] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A dam anti-seepage material suitable for extreme environments, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of self-expanding particles, 10-20 parts of epoxy resin, 0.2-2 parts of waterborne polyurethane curing agent and 1-10 parts of compounding agent.
2. The dam anti-seepage material suitable for extreme environments according to claim 1, characterized in that: The composite agent is prepared by mixing the following raw materials in parts by weight: 10-25 parts of propylene glycol, 4-10 parts of ethylene glycol, 2-10 parts of silane coupling agent, 1-5 parts of polyimide, 0.1-2 parts of carboxymethyl cellulose and 0.1-2 parts of surfactant.
3. The dam anti-seepage material suitable for extreme environments according to claim 2, characterized in that: The particle size of carboxymethyl cellulose is 500-800nm.
4. The dam anti-seepage material suitable for extreme environments according to claim 2, characterized in that: The surfactant is polysorbate-80, which is a yellow to amber viscous liquid.
5. The dam anti-seepage material suitable for extreme environments according to claim 2, characterized in that: The cross-linking agent is methylene bisacrylamide, which is in the form of white crystalline powder; the initiator is ammonium persulfate, which is white crystalline powder; and the accelerator is triethanolamine, which is a colorless to light yellow viscous liquid.
6. The dam anti-seepage material suitable for extreme environments according to claim 1, characterized in that: The plasticizer is one of phthalate and epoxidized soybean oil.
7. The dam anti-seepage material suitable for extreme environments according to claim 1, characterized in that: The toughening agent is nano-silicon dioxide, which is a white colloid and does not dissolve in liquid, but will form a colloidal suspension in the liquid.
8. The dam anti-seepage material suitable for extreme environments according to claim 1, characterized in that: The preparation method of the dam anti-seepage material comprises the following steps: Step S1: Mix epoxy resin, crosslinking agent and waterborne polyurethane curing agent in proportion, and stir evenly to obtain product ①; Step S2: Add the composite agent to the product ①, continue stirring, and obtain the product ② after it is completely dissolved and stirred evenly; Step S3: coating the obtained product ② on half of the area of the self-expanding particles, and forming a 5-10 mm thick sticky film on the surface of the self-expanding particles after coating.
9. The dam anti-seepage material suitable for extreme environments according to claim 2, characterized in that: The preparation method of the composite comprises the following steps: Step A1: adding propylene glycol and ethylene glycol to carboxymethyl cellulose in sequence, and continuing to stir, and obtaining a mixed solution after mixing evenly; Step A2: Add the silane coupling agent, polyimide and polysorbate-80 to the mixed solution in sequence, continue stirring, and obtain a composite agent after being evenly dispersed.
10. A method for applying the anti-seepage material prepared according to claims 1 to 9, characterized in that: The steps include: Step 1): Use leakage detectors and geological radar to inspect the dam to determine the specific location, scope and severity of the leakage area, and estimate the amount of dam anti-seepage materials required based on the size and depth of the leakage area; Step 2): According to the shape, size and geological conditions of the leakage area, plan the laying plan of the composite water fossil material, including the laying layer, thickness and sequence; Step 3): Divide the laying area into the bottom layer, middle layer and top layer according to the leakage area, and add geomembrane between each layer; Step 4): Use large-size gravel for the bottom layer, and small-size gravel for the middle and top layers to increase density and impermeability. The thickness of the bottom layer is 5-10cm, and the thickness of the middle and top layers is 3-5cm; Step 5): Build a working platform above the leakage area, and use underwater conveying equipment to transport the self-expanding particles that have just been coated with a sticky film to the leakage area and place them.
Citation Information
Cited By
High-toughness high-molecular flexible auxiliary anti-seepage protective material and preparation method thereof
CN120590852A
